Oral and dental health knowledge and attitudes among parents of children - ŞEN YAVUZ, BETÜL; KARGÜL, BETÜL (My University, 2023)
Objective: This study aims to evaluate parents’ knowledge and attitudes level on oral and dental health.Methods: One hundred and thirty parents of children aged 6-12 years, were invited to participate in the study. A 33-item questionnaire covering socio-demographic characteristics, dental attitude, dietary practices, tooth eruption, dental caries, and oral hygiene practices, was distributed to parents. The relationship between categorical variables was tested with the Chi-square test.Results: The sample comprised of 100 parents with a mean age of 37.1 ± 6.4. The knowledge and attitudes towards dental caries and oral health habits among parents did not differ significantly according to the parents’ gender, education level, or dental chair experience. There was a statistically significant difference in the responses of the first primary tooth and the first exfoliating primary tooth according to the gender of the parents (p=0.031, p=0.002, respectively). Although the education level of the parents did not affect the answers about the number of primary and permanent teeth, a statistically significant difference was found in the time of first primary tooth eruption (p=0.008).Conclusion: The study showed that parents do not have enough knowledge and awareness of dental caries and oral healthcare. Oral healthcare should be promoted as a part of general health and the awareness of the public should be increased.
Keywords: Diş Hekimliği; Klinik Bilimler; Pedodonti; Sağlık Bilimleri; Dentistry; Clinical Sciences; Pedodontics; Health Sciences; Klinik Tıp (MED); Klinik Tıp; DİŞ HEKİMLİĞİ, ORAL CERRAHİ VE TIP; Clinical Medicine (MED); CLINICAL MEDICINE; DENTISTRY, ORAL SURGERY & MEDICINE; Periodontoloji; Ortodonti; Ağız Cerrahisi; Diş Hijyeni; Dişçilik Hizmetleri; Diş Hekimliği (çeşitli); Periodontics; Orthodontics; Oral Surgery; Dental Hygiene; Dental Assisting; Dentistry (miscellaneous); General Dentistry